Utilization of Bagasse and Molasses for Polyhydroxybutyrate Production by Bacillus sp. SWU01 - Chuavong, Wisan; Chuklin, Katanyoo; Anansakulchai, Kanokpan; Leetian, Panisara; Ponprateep, Sirikwan; Vatanavicharn, Tipachai (Science Essence Journal, 2018)
ABSTRACT Polyhydroxybutyrate (PHB) is natural biodegradable thermoplastic belonging to the polyesters class. In physiological stress, PHB was produced and accumulated in intracellular granules of microorganisms as energy reserves in stress condition. Previously, we isolated the PHB producing bacteria, Bacillus sp. SWU01 from canned tuna wastewater. This research aimed to produce the PHB using bagasse and molasses as a carbon source by Bacillus sp. SWU01. To produce the PHB using bagasse, hydrolysis reaction was performed by cellulase or acid condition to get the reducing sugar. The results showed that enzymatic hydrolysis at the concentration of 0.45 FPU/mL for 48 h increased high content of reducing sugar. The PHB production using modified M9 medium, supplemented with reducing sugar from bagasse or molasses, by Bacillus sp. SWU01 was investigated. The highest PHB production of 2.01 g/L and PHB content constituted up to 60.54% of dry cell mass was obtained by reducing sugar from bagasse as carbon source at 48 h. To characterize functional group and monomer of polymer, the Fourier-transform infrared spectroscopy (FTIR), 1H- Nuclear magnetic resonance spectroscopy (NMR) and differential scanning calorimetry technique (DSC) revealed that the polymer extracted from the bacterial stain was PHB. These results suggested that Bacillus sp. strain SWU01 had potential to be the efficient PHB producer from biowaste. Keywords: Polyhydroxybutyrate, Sugarcane molasses, Reducing sugar, Bagasse, Bacillus sp.